Faktor-Faktor Yang Mempengaruhi Revaluasi Aset Tetap - S, Suharyono (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of banking in Indonesia has begun to increase as shown by the increasing number of Islamic This study aims to assess the factors that influence fixed asset revaluation in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange. The number of samples in this study was 11 companies with a sampling method using the purposive sampling method. This study uses secondary data obtained through the company's annual report. Data analysis uses logistic regression consisting of descriptive statistical analysis. The results of data analysis or logistic show that partially the variables leverage, deferred income tax and fixed asset intensity have a positive and significant effect on asset revaluation. While the variables of company size and liquidity do not have a significant effect on asset revaluation.